1999
DOI: 10.1046/j.1365-2133.1999.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

The cutaneous porphyrias: a review

Abstract: Many patients with cutaneous porphyria have curable or controllable disease; untreated porphyria may prove fatal. The genetic defects and mechanisms underlying porphyria are steadily being delineated, treatments have become more appropriate and genetic counselling is now more accurate. A summary of the basic diagnostic features, management and recent advances in the cutaneous porphyrias is presented, based on a workshop held by the British Photodermatology Group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 69 publications
0
30
0
3
Order By: Relevance
“…Scarring, hypertrichosis and hyperpigmentation can arise as a consequence of repeated skin eruptions. 11 The pathology of the cutaneous manifestations is mediated through direct photodynamic damage from absorbed ultraviolet light and oxygen free radical species production. 1 The enzymatic defects of HCP and VP are below the conversion of PBG to HMB, however it has been demonstrated that the addition of coproporphyrinogen III (HCP) and protoporphyrinogen IX (VP) lowered HMBS activity in human lymphoblasts and erythrocytes in vitro.…”
Section: Classification and Geneticsmentioning
confidence: 99%
“…Scarring, hypertrichosis and hyperpigmentation can arise as a consequence of repeated skin eruptions. 11 The pathology of the cutaneous manifestations is mediated through direct photodynamic damage from absorbed ultraviolet light and oxygen free radical species production. 1 The enzymatic defects of HCP and VP are below the conversion of PBG to HMB, however it has been demonstrated that the addition of coproporphyrinogen III (HCP) and protoporphyrinogen IX (VP) lowered HMBS activity in human lymphoblasts and erythrocytes in vitro.…”
Section: Classification and Geneticsmentioning
confidence: 99%
“…Bu da oksidatif hasara, DNA ve hücre membranının lipid peroksidasyonuna yol açarak, deri frajilitesi ve bül oluşumu ile sonuçlanır (11). Hastalık otozomal dominant geçişli olabildiği gibi olguların %80'i edinseldir ve multifaktöriyel etiyolojilidir (7). Hastalığın fenotipinin ortaya çıkması için bir veya birden fazla faktör gereklidir.…”
Section: Discussionunclassified
“…It is well documented that a clinically overt form of either subgroup is precipitated by risk factors (the most important of them being alcohol, iron, hepatitis and estrogen), which can contribute to inactivation of UD in the liver [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%